Improving Students’ Writing To The Eighth Grade Students By Using Clustering Technique - sulaiman sulaiman (English Language Education Department, Universitas Majalengka, 2022)
Abstract. This study aimed to optimize the students writing by implementating the clustering technique that technique help students to generate ideas. The method used the classroom action research as an appropriate method for this research. The subject in this research was done at SMP Negeri 02 Suhaid, Kapuas Hulu. This is a Junior High School which is located on Lintas Mensusai Street No.1 Mensusai, Kapuas Hulu Regency. The researcher conducted the research for 24 students’ of VIII class. In qualitative data finding based on the observation checklist and field note, the students very enthusiastic during teaching learning process and their showed positive attitude to the activities that were conducted by the researcher in clustering technique. Besides, there were some students who active and often asked the questions when they found some difficulties in writing. Moreover, in quantitative data finding had conclusion was that clustering technique could be used to improve the students’ writing skill. The students’ writing ability increased.